Maximising embryo production in endangered sheep breeds: in vitro procedures that complement in vivo techniques - Forcada, Fernando; Buffoni, Andres; Abecia, José Alfonso; Asenjo, B.; Palacin, José Ignacio; Vázquez, M.I.; Rodriguez Castillo, José del Carmen; Sanchez Prieto, L.; Casao, A. (Taylor & Francis, 2019)
This study investigated the use of previously superovulated ovaries as a source of oocytes, assessing the competence of them for in vitro embryo production. Two superovulatory treatments were performed: equine Chorionic Gonadotrophin (eCG) plus porcine Follicle-Stimulating Hormone (pFSH) in a single dose or the conventional protocol of six decreasing doses of pFSH. Thirty donor ewes of the endangered Ojalada breed were given either the simplified (group S; n=15) or the decreasing-dose (group D; n=15) treatments three times at intervals of ≥50 days. Ovaries were recovered on day 7 after the oestrus following the third treatment, just after embryo flushing, and the oocytes were collected to assess in vitro maturation, fertilisation and development to the blastocyst stage. The two superovulatory treatments did not differ in the mean number of oocytes selected for maturation (7.1±1.2 and 8.5±1.5 per ewe in the D and S groups, respectively). The oocytes recovered from ewes in Group D (87.5%) had a significantly (p<0.05) higher maturation rate than did those recovered from ewes in group S (75%), but no differences were found in fertilisation rate (94% and 94.6% in the D and S groups, respectively); both groups did not differ in their blastocyst rates and the total number of cells in in vitro-produced blastocysts. In the two experimental groups, 1.7 (D) and 1.8 (S) in vitro-produced blastocysts were generated per ewe, which indicate that it is feasible to combine in vivo and in vitro techniques to maximise embryo production in endangered sheep breeds.